Quality Analysis of Fermented Virgin Coconut Oil (VCO) Purified by Silica Slag Nickel Filtration - Nadyra Budiman; La Harimu; Rahmanpiu (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study has been conducted on Quality Analysis of Fermented Virgin Coconut Oil (VCO) with Purification using Nickel Silica Slag by Filtration. This study aims to describe the physical, organoleptic and chemical qualities of fermented VCO purified with nickel silica slag. The results showed that the VCO result value obtained was 9.33% (v/v), with the organoleptic test of Fermentation VCO before and after filtration, namely colors 3.93 and 4; smells 3.20 and 3.27, and tastes 2.80 and 2.80. Determination of the physical quality of Fermented VCO with clarity values before and after respectively, Transmission 90.0% and 92.0%. Determination of the chemical quality of Fermented VCO before and after Filtration, namely the moisture content value of 0.31% and 0.08%, respectively; the value of free fatty acid content is 0.17% and 0.15%; The peroxide values were 0.53 mg eq/kg and 0.52 mg eq/kg, and the saponification values were 189.16 mg KOH/g and 249.30 mg KOH/g. The results of the chemical quality analysis in this study are in accordance with SNI No. 7381 of 2008 and SNI No. 7431 of 2015. Therefore, it can be concluded that VCO absorbed using nickel silica slag can improve its physical and chemical qualities.